Ilusi Optis dalam Dunia Seni dan Desain - Jonata Witabora (Bina Nusantara University, 2012)
Visual is everything to do with vision. The ability of our brain to interpret visual is what we call visual perception. In the development of art and design, many artists and designers study visual perception and embody it in their works. One part of visual perception which attracts artists and made as the base on their work is optical illusion. This, in turn creates new streams in the world of art and design. Optical illusion is an anomaly in visual perception, a deceiving experience occurs beyond the control of the observer. Article maps out what optical illusions is, and identify a variety of optical illusions and their application in art and design.